Integration of spirituality in nursing care - Queiroz, Sandra (Servir, 2016)
Introduction Holistic Nursing care requires professionals to take into account the spirituality of those who they care for. However, the observation of current practice and daily records seldom show evidence about spiritual care. Methods From an integrative literature review, a reflection is provided on the factors that contribute to the scarce existing evidence of the integration of the spiritual dimension in the care provided by nurses. Development Incorporating the concepts of spirituality and religiosity, the spiritual needs and competence to provide spiritual care, topics that intend to help nurses to reflect on this subject in their professional life are presented. Conclusion Knowing the different factors that correlate to this issue, nurses must first take into account their own spirituality in order to improve care and provide evidence of the spiritual care performed.